2013
DOI: 10.3329/jssmc.v4i2.14406
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Regional Metasteses in Laryngeal Carcinoma

Abstract: Background: Regional metastases to the cervical lymph node is common in laryngeal carcinoma and this is also the most important prognostic factor of the disease. Objective: The purpose of the present study was to see the frequency of cervical metastases related to the sites of laryngeal carcinoma and also to see the relation between primary site and level of metastatic node as well as the relation between T and N stage of the tumour. Methodology: This cross sectional study was done in the Department of Otolary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…25 In supra-glottic cancers, the probability of cervical metastasis and the probability of delayed contralateral metastasis increase in direct proportion to the size of the primary lesion (i.e., the T stage). 5 showed N 0 was found 20(40.0%) cases followed by N1 and N2 which were 15(30.0%) cases and 13(26.0%) cases respectively. Kaur et al 16 study 58% (29 cases) were found to be N 0 stageconstituted by 58.3% of the supraglottic lesions, 100% of the glottis lesions and 51.5% of the transglottic lesions.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…25 In supra-glottic cancers, the probability of cervical metastasis and the probability of delayed contralateral metastasis increase in direct proportion to the size of the primary lesion (i.e., the T stage). 5 showed N 0 was found 20(40.0%) cases followed by N1 and N2 which were 15(30.0%) cases and 13(26.0%) cases respectively. Kaur et al 16 study 58% (29 cases) were found to be N 0 stageconstituted by 58.3% of the supraglottic lesions, 100% of the glottis lesions and 51.5% of the transglottic lesions.…”
Section: Resultsmentioning
confidence: 86%
“…Similarly, Jaimanti and Naresh 15 in a 10 year follow up of patients suffering from carcinoma larynx, found the incidence of supraglottic carcinoma was 55.94% of all laryngeal cancers followed by glottis (17.3%), transglottic (13.04%) and subglottis (3.62%). Ahsan et al 5 showed among 36 supraglottis cases, 26 (72.2%) cases showed metastasis. Out of 13 glottis cases, metastasis was found in 4 (30.8%) cases.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations